Protocolo para la atención de Enfermería intrahospitalaria dirigido a las gestantes afectadas por el consumo de drogas y su recién nacido (a). - Grettel Campos Vargas; Criss López Vargas; Vivian Montero Rodríguez (Universidad de Costa Rica, 2011)
The objective of this study is to present as a final result, a protocol for hospital care of pregnant women who are affected by drug use and their newborn. The sample was 15 workers of Emergency, Delivery Room, Gynecology, Obstetrics and Neonatology Services in Hospital San Vicente de Paul. To do this, first of all, we conducted a diagnosis, through the application of a self administered questionnaire, and then we coordinated meetings with the workers to develop the attention flowcharts that show the active involvement and commitment of Nursing toward this population, given as a result the treatment protocol. The results showed that the guided practice is viable, because it had human and material resources for its development. We conclude that the development of a protocol for hospital nursing care aimed at pregnant women with drug problems and their newborns, is a necessity in that hospital, due to the lack of regulations on this and the increase in cases related to theme.